Assessment and Economic Factors for Improving the Quality of Life: Theoretical Foundations, Methodological Approaches, Strategic Priorities - Oruntaeva, Asmat; Djumalieva, Elmira (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026, 2026)
Purpose: The purpose of this study was to identify the key aspects of assessing and improving the quality of life, as well as to use foreign practices to develop more effective strategies. Methodology: The study employed the methods of analysing models, statistical indices, and comparative data analysis, which enabled a greater understanding of the aspects of quality of life and its interrelationships in the context of Kyrgyzstan and other countries such as Kazakhstan, Turkmenistan, Azerbaijan, Uzbekistan, Tajikistan, Armenia. Findings: The study identified key factors affecting the quality of life of the population of Kyrgyzstan, among which the critical factors are economic development, social policy, environmental sustainability, and citizen engagement. The study was found that the creation of new jobs in sectors such as agriculture and tourism substantially increase the level of income and well-being of the population. Access to quality education and healthcare was also found to be critical to improving living conditions, especially in remote and rural areas. The study confirmed that environmental sustainability is a critical aspect, with modernisation of wastewater treatment systems and adoption of environmentally friendly technologies playing a significant role in ensuring the health of the population. Originality: As a result of the analysis, the study concluded that an integrated approach is required, which would consider the interaction of the above factors to improve the quality of life at all levels, thus necessitating the active engagement of both the state and society in joint initiatives.